2000
DOI: 10.3989/scimar.2000.64n4369
|View full text |Cite
|
Sign up to set email alerts
|

Considerations on the biology of <i>Plesionika edwardsi</i> (Brandt, 1851) (Decapoda, Caridea, Pandalidae) from experimental trap catches in the Spanish western Mediterranean Sea

Abstract: SUMMARY: In this study, the results obtained from three experimental trap shrimp (Plesionika edwardsi) fishing cruises in three different seasons are presented. They were carried out during a total of 50 days, of which 43 days were of effective fishing, covering the whole Spanish Mediterranean coast including the island of Alborán. On the whole, the fishing depth varied between 220 and 384 m, with a mean depth of 318 m. The target species appeared in 81% of the total samples carried out, with a mean yield (cpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
27
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 11 publications
5
27
0
Order By: Relevance
“…4, 2002 cies as well as other Pandalidae species. This confirms the reports of previous experimental trap surveys conducted in other areas: the South Pacific (King, 1986;Poupin et al, 1990), Indian Ocean (Lebeau, 1976), SouthEast Atlantic (Martins and Hargreaves, 1991;Biscoito, 1993;González and Santana, 1996), Mediterranean (Secci et al, 1994;García-Rodríguez et al, 2000). The traps attracted Pandalid shrimp at night when shrimp increase in abundance near the bottom in response to reduced predatory activity.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…4, 2002 cies as well as other Pandalidae species. This confirms the reports of previous experimental trap surveys conducted in other areas: the South Pacific (King, 1986;Poupin et al, 1990), Indian Ocean (Lebeau, 1976), SouthEast Atlantic (Martins and Hargreaves, 1991;Biscoito, 1993;González and Santana, 1996), Mediterranean (Secci et al, 1994;García-Rodríguez et al, 2000). The traps attracted Pandalid shrimp at night when shrimp increase in abundance near the bottom in response to reduced predatory activity.…”
supporting
confidence: 80%
“…In the present study, the yield obtained was similar to that reported for the western Mediterranean (García-Rodríguez et al, 2000) and did not show any significant change related to either season or depth. The high variability showed by CPUEs could be caused by both the distribution of P. edwardsii shoals along the continental slope and the size of the fishing rip used.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Firstly, we analyzed the population structure of all five species using data taken on board commercial trawlers and scientific vessels (MEDITS), testing differences in Mediterranean (GFCM). The inlet details GSA05 (Balearic Islands) and GSA06 (Northern Spain) showing the names of several ports from GSA06 and the different islands of the Balearic Archipelago mentioned in the work; the isobaths are 100 and 800 m. Red shrimp and caridean shrimp fishing grounds of GSA05 exploited by trawlers from GSA06 are also shown in dark grey and grey respectively (adapted from García-Rodríguez and Esteban, 1999;and García-Rodríguez et al 2000). size distributions between GSAs with the KolmogorovSmirnov test.…”
Section: Methodsmentioning
confidence: 99%
“…With the exception of a few vessels of GSA06 working in waters of GSA05 around Ibiza-Formentera (García-Rodríguez and Esteban 1999) and along the eastern slope of Mallorca and Menorca (García-Rodríguez et al 2000), the demersal fleets of the two purse-seine) in the geographical sub-areas Balearic Islands (GSA05) and Northern Spain (GSA06).…”
Section: Fisheriesmentioning
confidence: 99%